Organic Cultivation and Use of Medicinal Plants in Latin America - Madaleno, Isabel Maria (Pharmacognosy Communications)
The struggle to maintain good health is twice as diffi cult among the less wealthy, underemployed and unemployed citizens. This contribution examines the organic cultivation of medicinal species in front and backyards and their uses in ten Latin American cities and metropolitan regions. Three main categories of affl ictions are analyzed: (1) mild diseases, such as cough, colds, indigestion, conjunctivitis and diarrhoea; (2) the chronic health problems asthma and rheumatism; (3) serious troubles such as glaucoma, diabetes and cancer. Ancestral and domestic treatment practices using native and exotic fl ora are listed for each of the researched countries – Brazil, Chile, Argentina, Uruguay, Peru, Mexico, Cuba and Costa Rica – in order to provide a guide for interested peoples.
Keywords: Latin America; traditional medicines; domestic medicines; ethnopharmacology; ethnomedicine